Effectiveness of geogrid reinforcement in improvement of mechanical behavior of sand-contaminated ballast - Sadeghi, Javad; Tolou Kian, Ali Reza; Ghiasinejad, Hossein; Fallah Moqaddam, Mosarreza; Motevalli, Sepehr (Geotextiles and geomembranes, 2020)
Vertical stiffness and shear strength of ballasts are significantly degraded when contaminated with sands. There is a lack of solutions/studies related to strengthening ballast against sand contamination. Addressing this limitation, a comprehensive laboratory investigation was made on effectiveness of geogrid reinforcement for improvement of mechanical properties of sand-contaminated ballast. To this end, large-scale direct shear tests as well as plate load tests were conducted on geogrid-reinforced ballast samples prepared with different levels of sand contamination. The obtained results indicate that geogrid reinforcement considerably improves shear strength and vertical stiffness of contaminated ballast. A bandwidth was obtained for contamination levels in which ballast reinforcement is effective. Through examining geogrid with different aperture sizes and locations in the ballast layer, the best performance conditions of geogrid reinforcement were derived. The results were used to propose an effective method of ballast reinforcement and an efficient ballast maintenance approach in sandy areas.